2016
DOI: 10.12788/emed.2016.0042
|View full text |Cite
|
Sign up to set email alerts
|

Does Optic Nerve Sheath Diameter Ultrasonography Permit Accurate Detection of Real-Time Changes in ICP?

Abstract: While working abroad in a resource-limited environment, a patient was brought in after falling and hitting his head. Initially, the patient was awake and alert, but he gradually became minimally responsive, with a Glasgow Coma Scale score of 9. Your facility did not have computed tomography (CT) or magnetic resonance imaging (MRI), but did have a point-of-care ultrasound (US) machine. You measured the patient's optic nerve sheath diameter (ONSD) with the US and found a diameter of 4.5 mm in each eye. With this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Ellingsen et al showed that the CBF response started less than 30 s after the PaCO 2 began to increase, and that it required up to 2 min to reach a peak value 20 . Changes in the ICP are rapidly transmitted to the optic nerve sheath, with no apparent temporal lag 21 . In the present study, the EtCO 2 showed a peak value immediately after deflation, but the ONSD, which is an indicator of the ICP, showed the highest value after 5 min of deflation.…”
Section: Discussionmentioning
confidence: 99%
“…Ellingsen et al showed that the CBF response started less than 30 s after the PaCO 2 began to increase, and that it required up to 2 min to reach a peak value 20 . Changes in the ICP are rapidly transmitted to the optic nerve sheath, with no apparent temporal lag 21 . In the present study, the EtCO 2 showed a peak value immediately after deflation, but the ONSD, which is an indicator of the ICP, showed the highest value after 5 min of deflation.…”
Section: Discussionmentioning
confidence: 99%